BUILDING A LEARNING ORGANISATION IN INDONESIAN INSTITUTIONS OF HIGHER EDUCATION - Hardianto, Eddy Setyanto, Antonius Kiritin, Burhan & Linda Ika Mayasari (International Journal of Research Science and Management, 2017)
Facing serious competition in present days every organisation is supposed to start transforming into a Learning Organization. Especially for those universities and colleges the main goal of that is to implement the “tri dharma” (three principles) transforming to a Learning Organization has become really inevitable. In our days institutions of higher education are required to be acknowledged world wide. By applying the Learning Organisation structure in these institutions the satisfaction of the whole community will be increased. In the process of building up a Learning Organisation the management has key role. Transformative leadership is needed that is commited to the comunity as a whole to realise a Learning Organisation within the institution. The barriers in realizing a learning organisation in Indonesian institutions of higher education among other factors are the management itself and the condition of the existing infrastructure of the institution.